Integration from below: Mexicans and other Latinos in the US labor market - LEVINE, Elaine (Papeles de Población; Vol. 12 Núm. 47 (2006): Papeles de Población, 2006)
In this article I shall analyze what I consider to be a certain degree of de facto labor market integration between Mexico and the US, which was further accentuated by Nafta, under conditions that are mostly disadvantageous for Mexican migrant workers, in terms of the US context. In the first part of the article I shall briefly analyze labor market conditions in Mexico to explain why low-waged jobs in the US are so attractive to Mexican migrants. I shall then proceed to analyze labor market outcomes for Mexicans and other recent Latino immigrants to the US. I will also look at the relative socioeconomic status of different groups of Latinos and compare their educational attainment, occupational profiles and incomes with those of the non-Hispanic population in the US.